Fancy Nancy - O'Connor, Jane; Preiss-Glasser, Robin (New York : HarperCollins, 2006)
A young girl who loves fancy things helps her family to be fancy for one special night
Keywords: Individuality -- Fiction; Costume and dress -- Fiction; Manners and customs -- Fiction; Family life -- Fiction; Individuality -- Juvenile fiction; Clothing and dress -- Juvenile fiction; Manners and customs -- Juvenile fiction; Family -- Juvenile fiction